IN-DEPTH LEARNING EVALUATION IN PREPARING THE GOLDEN GENERATION OF 2045 THROUGH CHARACTER EDUCATION - Ernawati Zusiana; Yuli Prihatni; Ari Setiawan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Deep learning as an important framework for cultivating a resilient and character-driven golden generation. This study seeks to evaluate the role of deep learning in preparing the golden generation of 2045 through character education. This study was conducted at Sekaran Public Elementary School. The research period was from October to December. The sample consisted of seven teachers. The sampling technique in this study used purposive sampling. Data were collected through questionnaires and observations. Data analysis techniques began with data collection, data reduction, data presentation, and conclusions. The results show that the six character components in deep learning synergize to form the foundation for developing human resources with strong character in preparing the golden generation. Character education helps students internalize values ​​such as democracy, discipline, honesty, creativity, tolerance, and responsibility. This study makes a significant contribution to enriching the literature on deep learning analysis, particularly in linking character education to realizing the vision of the golden generation of 2045.